2018
DOI: 10.11607/ofph.1581
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Type I and Type II Collagen Expression in Rat Mandibular Condylar Cartilage Associated with Aging and Dietary Loading

Abstract: Condylar cartilage is sensitive to the interplay between loading, aging, and sex of middle-aged and older rats. High loading of condylar cartilage increased the thickness of cartilage in younger rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Osteoarthritis can affect several joints, including the TMJ. The mandibular condylar cartilage (MCC) of the TMJ is a fibrocartilaginous tissue which contains both type I and type II collagen (Orajarvi et al 2018;Wadhwa and Kapila 2008). The major role of the MCC is to support and distribute functional loads, allowing a frictionless motion and avoiding the breakdown of the cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis can affect several joints, including the TMJ. The mandibular condylar cartilage (MCC) of the TMJ is a fibrocartilaginous tissue which contains both type I and type II collagen (Orajarvi et al 2018;Wadhwa and Kapila 2008). The major role of the MCC is to support and distribute functional loads, allowing a frictionless motion and avoiding the breakdown of the cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Other models of reduced masticatory activity have been established by changing only the consistency of the diet, i.e. use of a powdery, paste or liquid diet [11,[13][14][15][16][17][18][19]. Bruxism is a normal activity for rodents, in order to keep the incisors sharp.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, few investigations have examined the relationship between food consistency and the TMJ response in models involving older animals. Orajärvi et al [18] reported that the characteristics of the TMJ condylar cartilage were correlated with loading, aging, and sex in older rats. In contrast, no studies have investigated the relationship between condylar bony change and food consistency in models involving older animals.…”
Section: Introductionmentioning
confidence: 99%
“…Three different measurements for the MCC thickness were made, one in the middle of the thickest portion of the middle third, and one 200 µm anterior and one 200 µm posterior to this line. The number of cartilage cells was measured by counting the cells that intersected these three lines [28]. The result of three measurements per section of condyle 100× magnification resulted in a total of 6 measurements per animal, and the mean value was then calculated.…”
Section: Group 4 (C/g)mentioning
confidence: 99%